2013
DOI: 10.1002/jms.3279
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of the designer benzodiazepine flubromazepam and preliminary data on its metabolism and pharmacokinetics

Abstract: The appearance of pyrazolam in Internet shops selling 'research chemicals' in 2012 marked the beginning of designer benzodiazepines being sold as recreational drugs or 'self medication'. With recent changes in national narcotics laws in many countries, where two uncontrolled benzodiazepines (phenazepam and etizolam), which were marketed by pharmaceutical companies in some countries, were scheduled, clandestine laboratories seem to turn to poorly characterized research drug candidates as legal substitutes. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 18 publications
5
77
0
Order By: Relevance
“…[3] Flubromazolam (8-bromo-6-(2-fluorophenyl)-1-methyl-H- [1,2,4]triazolo- [4,3a][1,4]benzodiazepine; Fig. 1) is the triazole analogue of flubromazepam, [4] and it is structurally related to triazole benzodiazepines such as alprazolam and triazolam.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Flubromazolam (8-bromo-6-(2-fluorophenyl)-1-methyl-H- [1,2,4]triazolo- [4,3a][1,4]benzodiazepine; Fig. 1) is the triazole analogue of flubromazepam, [4] and it is structurally related to triazole benzodiazepines such as alprazolam and triazolam.…”
Section: Introductionmentioning
confidence: 99%
“…10 Acutely, NPS benzodiazepines have similar clinical effects to established compounds such as diazepam, with sedative, anxiolytic, hypnotic, and anticonvulsant properties. Some users of NPS benzodiazepines report that they have much longer durations of actions and effects than established agents, and several compounds have long half lives (flubromazepam, for example, having a half life of 100 hours 63 ). While this reduces dependency potential, unwanted effects can persist for a long time and there are greater risks of accidental overdose.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…Research into the pharmacokinetics and pharmacodynamics of flubromazepam is pretty scarce with only one study found on Pubmed at the time this review where one of the authors actually ingested 4mg of the drug to obtain data [103]. Flubromazepam has been reported as having a half-life of more than 106 hours with metabolites detectable by LC-MS/MS for up to 28 days after consumption.…”
Section: Benzodiazepines: Flubromazepammentioning
confidence: 99%
“…Flubromazepam (26) is the second of the class to be put on the market and was a drug candidate described first in 1962 by Sternbach et al Its potency is said to be possibly higher than those of bromazepam, diazepam and nitrazepam [102,103].…”
Section: Benzodiazepines-flubromazepammentioning
confidence: 99%
See 1 more Smart Citation